SYNTHESIS OF VIRUS-SPECIFIC POLYMERS IN ADENOVIRUS-INFECTED CELLS: EFFECT OF 5-FLUORODEOXYURIDINE - Flanagan, John F. (The Rockefeller University Press, 1962)
Biochemical synthesis in adenovirus-infected HeLa cells was studied utilizing 5-fluorodeoxyuridine (5-FUDR), a potent inhibitor of deoxyribonucleic acid production. Synthesis of saline-soluble DNA and infectious virus was completely suppressed by addition of the analogue to cells as late as 10 hours after infection. The inhibitory effect of this compound was totally reversed by addition of 10(–6) M thymidine to the culture medium. Synthesis of DNA essential for virus production began 10 hours after infection and was completed by 16 hours after infection. These data support the hypothesis that the saline-soluble DNA is a precursor of infectious virus particles. Studies of antigen production indicated that formation of virus-specific proteins was directly dependent upon synthesis of DNA.